Rigorous Analytical and Numerical Analysis of Unsteady Free Convection Flow Over a Stretching Sheet with Thermal Radiation and Chemical Reaction - Gandharv Jha (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper presents a comprehensive analytical and numerical study of unsteady free convection flow over a continuously stretching sheet under the simultaneous influences of thermal radiation and a first–order chemical reaction. The governing equations are derived under the Boussinesq approximation and reduced via similarity transformations to a set of nonlinear ordinary differential equations. Advanced analyti- cal techniques, including the Adomian Decomposition Method (ADM) and the Homotopy Analysis Method (HAM), are employed to obtain convergent series solutions. Rigorous convergence analysis and resid- ual error estimates are provided, and the analytical results are val- idated by a high–accuracy Runge–Kutta–Fehlberg shooting method. Extensive parametric studies are conducted to examine the effects of magnetic damping, radiative heat transfer, and chemical reaction on the velocity, thermal, and concentration profiles. The findings offer deep insight into the complex interactions among multiple physical processes and serve as a benchmark for future investigations.